Histopathological features of incidental appendectomy specimens obtained from living liver donors - Sami Akbulut,; Cemalettin Koç,; Barış Sarıcı,; Mehmet Özcan,; Emine Şamdancı,; Sezai Yılmaz, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To determine the histopathological features of incidental appendectomy specimens obtained from living liver donors (LLDs)Materials and Methods: Between September 2005 and November 2018, 1910 LLDs underwent living donor hepatectomy at our institute. Incidental appendectomy together with living donor hepatectomy (LDH) was performed in 170 LLDs. The decision for incidental appendectomy was made by experienced gastrointestinal surgeons. Histopathological features of the appendectomy specimens were analyzed by two pathologists, and the following parameters were retrospectively evaluated: age, sex, appendix length (mm), appendix width (mm), presence of appendicitis, and unusual histopathological findings.Results: Histopathological findings from 97 male and 73 female LLDs aged between 18 and 64 (median: 30) years were retrospectively examined. The length of the appendix vermiformis ranged from 25 to 120 (median: 70) mm, whereas its width ranged from 4 to 13 (median: 6) mm. The following histopathological findings were observed: normal appendix vermiformis (n=137), fibrous obliteration (n=13), acute appendicitis (n=5), enterobius vermicularis (n=4), lymphoid hyperplasia (n=4), low-grade appendiceal mucinous neoplasm (n=2), mucinous cystadenoma (n=1), grade 1 neuroendocrine tumor (n=1), hyperplastic polyp (n=1), enterobius vermicularis with fibrous obliteration (n=1), and acute appendicitis with eosinophilic infiltration (n=1).Conclusion: This study showed that a careful inspection of the abdominal cavity was useful, and appendectomy should be performed when required. In addition, even if the macroscopic appearance of the appendectomy specimens is normal, histopathological evaluations facilitate an early diagnosis of numerous unusual appendiceal diseases.Cite this article as: Akbulut S, Koç C, Sarıcı B, Özcan M, Şamdancı E, Yılmaz S. Histopathological features of incidental appendectomy specimens obtained from living liver donors. Turk J Gastroenterol 2020; 31(3): 257-63.